Strengthening Implementation of Merdeka Belajar Policy Through the Role of Mover Teacher - Yulianti, Riska; Lestari, Nur'im Septi; Wahyuningrum, Paulina Maria Ekasari; Nengsih, Luluk Wahyu; Rosadi, Asep (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
The purpose of this research was to find out the strengthening of the implementation of Merdeka Belajar policy through the role of the mover teacher. The research method used in this research was qualitative. The type of research was library research. The data analysis technique used in this research was content analysis technique. The research results obtained were then presented descriptively in accordance with the research problems and objectives. The results of this research showed that the strategic role of the mover teacher, namely as a mover force in a school based on teaching experience in school, which basically moves all components of education to be actively involved in improving the quality of education, The mover teacher in Merdeka Belajar is expected to be able to direct and shape students in developing their personality as a whole, The mover teacher changes the pattern of educational transformation from a centralized pattern towards decentralization with the mover teacher as an agent and the school as the leader of the transformation process, The mover teacher is a learning leader in Merdeka Belajar who has the ability to move the educational ecosystem to realize learner-centered education.